Norm method to define and evaluate robustness of self-compacting concrete due to component quantity variations. (10th February 2018) - Zuo, Wenqiang; Liu, Jiaping; Tian, Qian; Xu, Wen; She, Wei; Miao, Changwen
Highlights: The variations of water and aggregate contents strongly affect the fresh properties of SCC. The robustness of the hardened properties of SCC is higher than the fresh-related properties. The norm method can evaluate the robustness of SCC in a more intuitive way. Decent consistency can be found between the norm method and previous evaluation method. Abstract: Presently, self-compacting concrete (SCC) has been widely used and has many incomparable advantages compared to the traditional vibrated concrete. While it also has many disadvantages among which the robustness of SCC seems to be a serious problem at the production stage. In this study, both the fresh and hardened properties of a low binder content SCC were studied in the cases of the quantity variations of components. Meanwhile, a new robustness assessment method based on the concepts of linear algebra (using norm analysis of vectors) was proposed in order to define and evaluate the robustness of SCC. The results show that the robustness of the hardened properties is higher than that of the fresh-related properties. Additionally, by adopting the proposed method, the robustness of the SCC mixtures can be described and evaluated in a more intuitive way and both the variations of moisture content and aggregate quantities, such as the volume fraction and the gradation, strongly affect the fresh properties of the low-binder SCC. Finally, a good consistency was found between the proposed method and a previous robustness evaluation method thus proving that the proposed methods can be regarded as a concise and effective tool to define and evaluate the robustness of the SCC mixtures.